Investigation into various aspects of radiolabelling somatostatin peptide derivatives with 68Ga eluted from a SnO2-based 68Ge/68Ga generator - Prince, Deidre Mabel (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.